The interface between research on individual difference variables and teaching practice: The case of cognitive factors and personality - Biedroń, Adriana; Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2016)
While a substantial body of empirical evidence has been accrued about the role of individual differences in second language acquisition, relatively little is still known about how factors of this kind can mediate the effects of instructional practices as well as how empirically-derived insights can inform foreign language pedagogy, both with respect to shaping certain variables and adjusting instruction to individual learner profiles. The present paper is an attempt to shed light on the interface between research on individual difference factors and teaching practice, focusing upon variables which do not easily lend themselves to external manipulation, namely intelligence, foreign language aptitude, working memory and personality, with the role of the last of these in language learning being admittedly the least obvious. In each case, the main research findings will briefly be outlined, their potential for informing instruction will be considered, and, in the final part, the caveats concerning practical applications of research on the variables in question will be spelled out.